Hubungan Konsep Diri dan Komunikasi Interpersonal dengan Motivasi Belajar pada Siswa Sekolah Menengah Pertama - Khairawani Luthfi; Saiful Akhyar Lubis; Nina Siti Salmaniah Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research aims to find out the relationship of Self-Concept and Interpersonal Communication with Learning Motivation in State Junior High School Students 2 Tanjung Tiram Bara Regency, with a population of 167 students. The research sample numbered 33 students. The method used in this study is a quantitative method with sampling techniques using the Stratified Random Sampling Proportional Technique. Abstract is written briefly and factually, covering research objectives, research methods, results and conclusions. Abstracts are written in one paragraph; written in two languages (Indonesian and English); abstract lengths ranging from 150 - 200 words. Avoid referrals and unusual abbreviations. Cambria 10, with one line spacing (1) spacing. In Indonesian. The instrument used is the Likert Scale model. Data collection techniques use three scales consisting of the Self-Concept Scale, Interpersonal Communication and Learning Motivation. The analysis technique used is multiple regression. Based on the results of the study concluded that: 1) Self-concept is positively related to student learning motivation indicated by a correlation coefficient of R = 0.768. Where the contribution of variable X1 to variable Y amounted to R2 = 58.9%. 2) Interpersonal communication is positively related to student learning motivation indicated by a correlation coefficient of R = 0.584. Where the contribution of variable X2 to Y amounted to R2 = 34.1%. 3) Self-Concept and Interpersonal Communication together have a relationship to learning motivation of R = 0.783. Where the variable contribution of X1 and X2 to Y amounted to R2 = 61.3%. From these results it can be said that the higher the Self-Concept and Interpersonal Communication, the higher the motivation to learn, and vice versa the lower the Self-Concept and Interpersonal Communication, the lower the student's Learning Motivation